Can We Improve Patient Safety? - Corbally, Martin Thomas (Frontiers in Pediatrics, 2014)
Despite greater awareness of patient safety issues especially in the operating room and the widespread implementation of surgical time out (WHO),errors, especially wrong site surgery, continue. Most such errors are due to lapses in communication where decision makers fail to consult or confirm operative findings but worryingly where parental concerns over the planned procedure are ignored or not followed through. The WHO surgical pause / Time Out aims to capture these errors and prevent them but the combination of human error and complex hospital environments can overwhelm even robust safety structures and simple common sense. Parents are the ultimate repository of information on their child's condition and planned surgery but are traditionally excluded from the process of Surgical pause and Time Out perhaps to avoid additional stress. In addition surgeons, like pilots, are subject to the phenomenon of "plan continue fail" with potentially disastrous outcomes.